2010
DOI: 10.1002/mabi.200900175
|View full text |Cite
|
Sign up to set email alerts
|

Entropically Driven Self‐Assembly of Lysinibacillus sphaericus S‐Layer Proteins Analyzed Under Various Environmental Conditions

Abstract: S-Layer proteins are an example of bionanostructures that can be exploited in nanofabrication. In addition to their ordered structure, the ability to self-assembly is a key feature that makes them a promising technological tool. Here, in vitro self-assembly kinetics of SpbA was investigated, and found that it occurs at a rate that is dependent on temperature, its concentration, and the concentration of calcium ions and sodium chloride. The activation enthalpy (120.81 kJ . mol(-1)) and entropy (129.34 J . mol(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…A detailed discussion of the specific role of Ca 2+ -ions (and other divalent cations) associated with conformational changes within a protein and a more generic role mediating interactions between proteins (and supports) may be found in references [27,28,29]. The reassembly is entropy-driven and a fascinating example of matrix assembly following a multistage, non-classical pathway in which the process of S-layer protein folding is directly linked with assembly into extended clusters [13]. In a theoretical approach, the formation of an S-layer lattice with square (p4) lattice symmetry (as for SbpA) was investigated by assuming both non-specific attractive and specific directional bonds for the monomers [30,31,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed discussion of the specific role of Ca 2+ -ions (and other divalent cations) associated with conformational changes within a protein and a more generic role mediating interactions between proteins (and supports) may be found in references [27,28,29]. The reassembly is entropy-driven and a fascinating example of matrix assembly following a multistage, non-classical pathway in which the process of S-layer protein folding is directly linked with assembly into extended clusters [13]. In a theoretical approach, the formation of an S-layer lattice with square (p4) lattice symmetry (as for SbpA) was investigated by assuming both non-specific attractive and specific directional bonds for the monomers [30,31,32].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro self-assembly studies in solutions showed that self-assembly products (flat sheets, cylinders) are formed during dialysis of the disrupting agent against selected buffer solutions (ionic strength and pH) [2]. Kinetic measurements at different temperatures indicated that the assembly process is entropy driven with a rapid initial phase, at which oligomeric precursor patches acting as nucleation sites are formed, and a consecutive slow phase of crystal growth [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Due to its excellent ability to regularly assemble monomers in aqueous environments, Slp can spontaneously self-assemble on air-water interfaces, solid supports, or liposomes or in suspension and solution, by an entropydriven process (Figure 1). 5,6 This feature enables a wide range of potential applications of Slp in nanomedicine, bioactive drug delivery, and gene drug delivery. As a result, Slp-coated liposomes have received increasing attention in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…To produce SbpA under non-denaturing conditions, we amplified the SbpA gene from the genomic DNA of Lysinibacillus sphaericus (ATCC number 4525) [7, 9], cloned it into the pET28a vector following an established protocol [9] and expressed the protein in E. coli strain HMS174(DE3) (EMD Biosciences). Once induced, cells were cultured for 18 hours at 18°C, and then harvested and lysed as described before [15].…”
Section: Resultsmentioning
confidence: 99%